LARGE-SCALE MANTLE METASOMATISM: A RE-OS PERSPECTIVE - Chesley J.; Ruiz J.; Righter K. (My University, 2004)
There is a debate on the behavior of Re and Os during mantle metasomatism. Some argue that the mantle can acquire high 187Os/188Os (0.15 to >1.0) either directly from metasomatic events or by the growth of 187Os from 187Re over time. However, any suggestions of subduction-related Os metasomatism producing whole-scale elevation of the mantle to 187Os/188Os values greater than 0.15 need to be supported by comparisons of increased Re and Os concentrations and isotopic ratios, with like and consistent increases in elements (i.e., Ba, B, Rb) and isotopic ratios (i.e., Nd, Pb, Sr) known to be affected by metasomatic processes. All of the samples in the literature, either xenoliths or minerals (sulfides, pyroxene, phlogopite or amphibole) that are thought to represent the products of mantle metasomatism, follow a clear correlation of increasing Re/Os with decreasing Os concentration. This inverse correlation requires enrichment in Os concentrations in the metasomatizing agent by two to four orders of magnitude relative to the original subduction component in order to substantially elevate 187Os/188Os, eliminating sediment or slab melts as an effective metasomatic component. To date there is no evidence to support conclusions that Os metasomatism, either directly or by a two-stage process involving Re metasomatism and 187Os growth over time, will substantially change the 187Os/188Os of the mantle to values >0.15. When other isotopic systems are considered along with Os, in metasomatism-based models, these models are not plausible. Consequently, large-scale mantle melts should reflect near-chondritic values. The recognition of the robustness of the Re–Os system will allow for the discrimination of different mantle and crustal reservoirs involved in magmatic processes.